In vitro hypoglycemic effects of unripe and ripe fruits of Musa sapientum - Somnath Devidas Bhinge; Mangesh Anil Bhutkar; Dheeraj Suhas Randive; Ganesh Hindurao Wadkar; Tejashri Suresh Hasabe (Universidade de São Paulo, 2018)
ABSTRACT The present study was undertaken to verify the hypoglycemic potential of unripe and ripe fruit extracts of Musa sapientum by using various in-vitro techniques, namely glucose adsorption capacity, glucose diffusion, amylolysis kinetics and glucose transport across the yeast cells. The results revealed that the unripe and ripe fruit extracts of Musa sapientum adsorbed glucose and the adsorption of glucose increased remarkably with an increase in glucose concentration. There were no significant (p≤0.05) differences between their adsorption capacities. In the amylolysis kinetic experimental model the rate of glucose diffusion was found to be increased with time from 30 to 180 min and both extracts exhibited significant inhibitory effects on the movement of glucose into external solution across the dialysis membrane as compared to control. The plant extracts also promoted glucose uptake by the yeast cells and enhancement of glucose uptake was dependent on both the sample and glucose concentration. The hypoglycemic effect exhibited by the extracts was observed to be mediated by inhibiting α-amylase, inhibiting glucose diffusion by adsorbing glucose and by increasing glucose transport across the cell membranes as revealed by an in-vitro model of yeast cells.